Nutrient and sediment transport from two different agriculture land uses - Muniandy, Josilva M. (2014)
For the past decades, the number of research on Non Point Source (NPS) pollution has increased due to its nature being the major source of pollution to water degradation around the world. The study of NPS in Malaysia is scarce especially in agricultural areas. This research aims to provide quality and quantity of runoff pollutant loadings from an agricultural farm at a plot scale. Two plots were constructed at different land use (fruit orchard and vegetable farm). Tipping bucket flow gauges were installed at the end of each slope to measure runoff volume and collect water sample. The water samples were collected over a period of three months, immediately following rainfall events. Nine water parameter (Nitrite, Nitrate, Ammonia, Total Nitrogen, Phosphate, Total Phosphorus, Chemical Oxygen Demand, Total Suspended Solid, pH) analyses were conducted by using the DR5000 UV-Spectrometer. Result indicated that Total Suspended Solid (TSS) from fruit orchard is much higher while the nutrient and Chemical Oxygen Demand (COD) in vegetable farm is higher in comparison. COD is higher in vegetable farm runoff than fruit orchard since organic fertilizers such as chicken manure are applied. Runoff collected is much higher in the fruit orchard since no effective cover crop there. Overall, the results confirmed that runoff waters from agricultural areas are heavily polluted and could affect the nearby receiving water in long term if it is not monitored and controlled.